Parental behaviour and brood integrity in amalgamated broods of the Common Eider - Beauchamp, Guy (Wildfowl, 2000)
Post-hatch brood amalgamation was examined in the Common Eider (Somateria mollissima) along the shorelines of the St. Lawrence estuary, Quebec, Canada. Broods typically contained a large number of ducklings and several females in attendance. The amount of time allocated to foraging, vigilance, and other activities by brooding females failed to vary as a function of the number of ducklings. In addition, abandoned ducklings were readily adopted by brooding females suggesting that parental care is not constrained by the presence of additional ducklings. Parental behaviour also varied little in response to the presence of additional females. Preening on shore, however, increased in frequency with the number of females perhaps because broods aggregated more often in safer sites. Losses of ducklings occurred in several broods in one of three ways: (1) when ducklings straggled behind during foraging activities, (2) when broods aggregated temporarily and more rarely (3) when females voluntarily abandoned ducklings. Such losses suggest that integrity may be difficult to maintain in amalgamated broods. The extent to which lost ducklings are predisposed to be abandoned as a result of sickness or severe malnutrition, for instance, remains to be investigated.